(untitled) (University Arena, 2025)
Background. Physical exercises have been practiced for prophylactic and curative purposes since ancient times.Based on the principle of combining prophylactic and therapeutic means in motion therapy, we can associate with to the means of medical gymnastics other therapeutic methods, such as therapeutic swimming, which strengthen the action and increase the capacity of the specific means. Objectives. The aim of the study was to select and structure the specific means of kinetotherapy and therapeutic swimming, using multiple possibilities of correlation and combination, in order to help improving the recovery process in ankylosing spondylitis (for reducing the recovery time and increasing the efficiency Methods. The research methods used were: documenting by studying specialized material; Case study, applied to a single subject, a student diagnosed with ankylosing spondylitis; Measurement and testing method necessary to objectify all processes undergoing scientific research. The study was conducted over an university year, and was divided into three stages: in the first stage, the initial evaluation of the subject, the second stage, the development of the kinetotherapeutic intervention program, and the last stage of the final evaluation, the processing of the test data and the interpretation of the results . Results. Kinetic treatment has played an important role in improving ankylosing spondylitis. The medical gymnastics programs and the therapeutic swimming programs had as a reference: the local postural re-education, regaining the figure, regaining strength; and encompassed means to relieve pain, muscular toning and increase mobility of affected joints. Conclusion. Physical therapy was very important for regaining the mobility and contributed a lot to resuming the normal daily activities of the patient. Thus, for a complete success of the treatment, physical exercise should be a daily activity even after the disease enters remission, throughout the complex therapy through motion.